2021
DOI: 10.1590/s0004-2803.202100000-09
|View full text |Cite
|
Sign up to set email alerts
|

Body Iron Status Indicators and Inflammation Indicators During Inflammatory Bowel Disease Therapy in Children and Adolescentes

Abstract: BACKGROUND: The treatment of patients with inflammatory bowel disease (IBD) consists of the induction and maintenance remission of the disease. Iron status indicators would be useful for the diagnosis of iron deficiency anemia, whereas the inflammation indicators would be for the diagnosis of chronic disease anemia. OBJECTIVE: To assess body iron status indicators and inflammation indicators during the treatment of IBD, consisted of conventional or infliximab therapy in children and adolescents. METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“… 7 MiRs have also been confirmed to play a regulatory role in cardiac hypertrophy, myocardial fibrosis, and other cardiovascular diseases. 8 Many studies have confirmed that certain miRs are key regulators of DCM, including miR‐34a, miR‐125b, 9 miR‐144, 10 and miR‐410‐5p. 11 MiR‐494 is located on chromosome 14q32.31 and was initially discovered due to up‐regulated expression in human retinoblastoma tissues.…”
Section: Introductionmentioning
confidence: 99%
“… 7 MiRs have also been confirmed to play a regulatory role in cardiac hypertrophy, myocardial fibrosis, and other cardiovascular diseases. 8 Many studies have confirmed that certain miRs are key regulators of DCM, including miR‐34a, miR‐125b, 9 miR‐144, 10 and miR‐410‐5p. 11 MiR‐494 is located on chromosome 14q32.31 and was initially discovered due to up‐regulated expression in human retinoblastoma tissues.…”
Section: Introductionmentioning
confidence: 99%